Common and unique effects of HD-tDCS to the social brain across cultural groups. (October 2019) - Martin, A.K.; Su, P.; Meinzer, M.
Abstract: Cultural background influences social cognition, however no study has examined brain stimulation differences attributable to cultural background. 104 young adults [52 South-East Asian Singaporeans (SEA); 52 Caucasian Australians (CA)] received anodal high-definition transcranial direct current stimulation (HD-tDCS) to the dorsomedial prefrontal cortex (dmPFC) or the right temporoparietal junction (rTPJ). Participants completed tasks with varying demands on self-other processing including visual perspective taking (VPT)and episodic memory with self and other encoding. At baseline, SEA showed greater self-other integration than CA in the level one (line-of-sight) VPT task as indexed by greater interference from the alternate perspective. Anodal HD-tDCS to the dmPFC resulted in the CA performing closer to the SEA during egocentric perspective judgements. Baseline performance on level two (embodied rotation) VPT task and the self-reference effect (SRE) in episodic memory was comparable between the two groups. In the combined sample, HD-tDCS to the rTPJ decreased the interference from the egocentric perspective during level two VPT and dmPFC HD-tDCS removed the SRE in episodic memory. Stimulation effects were comparable when baseline performance was comparable. When baseline performance differed, stimulation differences were identified. Therefore, social cognitive differences due to cultural background are an important consideration in social brain stimulation studies. Highlights: South-East Asians were influenced by the alternate perspective to a greater extent during visual perspective taking. Anodal HD-tDCS to the dmPFC shifted Caucasians closer to the baseline performance of South-East Asians. Anodal HD-tDCS to the dmPFC removed the self-reference effect in episodic memory in both cultural groups. Anodal HD-tDCS to the dmPFC reduced overall memory performance in the South-East Asians but not in the Caucasian group. Anodal HD-tDCS to the rTPJ reduced egocentric interference during visual perspective taking in both cultural groups.